2022
DOI: 10.3390/ma15228138
|View full text |Cite
|
Sign up to set email alerts
|

Towards Investigating the Effect of Ammonium Nitrate on the Characteristics and Thermal Decomposition Behavior of Energetic Double Base NC/DEGDN Composite

Abstract: This research work aimed to elaborate on a new modified double-base propellant containing nitrocellulose (NC), ammonium nitrate (AN), and diethylene glycol dinitrate (DEGDN). The developed AN/NC-DEGDN formulation was successfully obtained through a casting process and fully characterized in terms of its chemical structure, morphological features, and thermal behavior. Beforehand, theoretical calculation by the CEA-NASA program was applied to select the optimal composition of the formulation. Experimental findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Therefore, it is recommended to utilize a minimum of three distinct heating rates to accurately determine the various kinetic parameters associated with the decomposition process. 32–34 In a non-isothermal, isoconversion method, at a constant conversion ( α ), the reaction rate ( k ( T )) is affected by the temperature (eqn (1)): 14 where f ( α ) is the differential model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is recommended to utilize a minimum of three distinct heating rates to accurately determine the various kinetic parameters associated with the decomposition process. 32–34 In a non-isothermal, isoconversion method, at a constant conversion ( α ), the reaction rate ( k ( T )) is affected by the temperature (eqn (1)): 14 where f ( α ) is the differential model.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Boukeciat et al . 14 investigated double base propellants, which consisted of 60% ammonium nitrate, 10% nitrocellulose, and 30% diethylene glycol dinitrate, to assess their thermal performance potential. The inclusion of ammonium nitrate not only lowered the activation energy of the propellant but also elevated the heat content during decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…A greater influence of DEGDN can be observed for the TBC modified granules, when the lowest activation energy value of the decomposition process was obtained. The activation energy of NC-DEGDN system was about 135 kJ mol À 1 [54,55]. In contrast granules containing ATEC or TBC and DEGDN were characterized by a higher activation energy than binary system NC-DEGDN.…”
Section: Granulesmentioning
confidence: 95%
“…To overcome this disadvantage of AP and produce clean-burning propellants, AN is being tested. 1,[3][4][5] AN is a synthetic salt widely used in the chemical industry and agriculture. [6][7][8][9] The gaseous products of AN on thermal decomposition are chlorine-free and smokeless.…”
Section: Introductionmentioning
confidence: 99%
“…4 Touidjine et al 4 reported AN-based composite solid propellants containing polyurethane/nitrocellulose blends as a binder, metallic aluminum, IPDI curing agent, plasticizer, glycerin chain extender, and a silicon oil surfactant. Boukeciat et al 5 reported that AN (oxidizer)/diethylene glycol dinitrate-nitrocellulose containing double base solid propellants exhibited a lower thermal decomposition and kinetic characteristics than a diethylene glycol dinitrate-nitrocellulose composite with increased enthalpy of decomposition. AN as an oxidizer in solid propellants has been tested less because of its poor ignitability, low energy, low burning rate under low-pressure conditions, and hygroscopicity, limiting its use.…”
Section: Introductionmentioning
confidence: 99%